Long-term variations in intensity and location of the African Easterly Jet - Dezfuli, Amin (My University, 2009)
The mid-tropospheric African Easterly Jet (AEJ) is an important feature of the atmospheric circulation over West Africa. In this study the maximum intensity of AEJ and the corresponding latitude are obtained from NCEP reanalysis data for the period of 1948-2003. The analysis is confined to August, the month of peak rainfall. The interannual variability of the intensity and latitude of the jet core and the correlation between these two variables are then investigated. Previous studies consider the AEJ as a single atmospheric feature. Our study found a zonal double-core structure in AEJ suggesting to split it up into western (AEJ-W: 20W-5E) and eastern (AEJ-E: 5E-30E) components.The interannual analyses show a decrease in the average intensity of the AEJ-W in the mid-1970s, but no abrupt change in the latitude. The correlation between intensity and the corresponding latitude of AEJ-W was found to be insignificant. However, the intensity of the AEJ-E increased and latitude of AEJ-E decreased in the mid-1970s. The intensity and latitude in this case are strongly correlated (r=-0.57). The intensity of AEJ-W and AEJ-E are poorly correlated.The relationships of these two components of the AEJ with Low Level Westerlies (LLW: at 850 hPa and between 15W-15E), North Atlantic Oscillation (NAO) index and Atlantic Nino are also examined. The results suggest a positive correlation between intensity of the AEJ-W and LLW (r= 0.45) and their corresponding latitudes (r= 0.45). There is also a high positive correlation between the location of the maximum AEJ-E and LLW (r=0.65). The analyses show that the intensity of the AEJ-W is positively lag-correlated with the April-June NAO (r=0.38), while negatively correlated with July-August NAO (r=-0.42). However, the intensity of the AEJ-E and the latitude of the core of both components appeared to be poorly correlated with NAO. Finally, the seasonal Sea Surface Temperature Anomalies (SSTA) of March-April, averaged over the Atlantic Nino region (25W-5E and 2S-6N), was lag correlated with the intensity and latitude of the two jets. It shows a relatively significant lag-correlation only with the maximum intensity of the AEJ-E (r=0.31).
21st Conference on Climate Variability and Change, Phoenix , AZ, January 10-15, 2009